2018
DOI: 10.3389/fchem.2018.00243
|View full text |Cite
|
Sign up to set email alerts
|

The Human SLC7A5 (LAT1): The Intriguing Histidine/Large Neutral Amino Acid Transporter and Its Relevance to Human Health

Abstract: SLC7A5, known as LAT1, belongs to the APC superfamily and forms a heterodimeric amino acid transporter interacting with the glycoprotein CD98 (SLC3A2) through a conserved disulfide. The complex is responsible for uptake of essential amino acids in crucial body districts such as placenta and blood brain barrier. LAT1/CD98 heterodimer has been studied over the years to unravel the transport mechanism and the role of each subunit. Studies conducted in intact cells demonstrated that LAT1/CD98 mediates a Na+ and pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
232
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(236 citation statements)
references
References 111 publications
(190 reference statements)
4
232
0
Order By: Relevance
“…One distinct cluster upregulates the SLC7A3 and SLC7A5 genes. SLC7A5 is a known thyroid hormone transporter for its T3/T4 states (Scalise et al, 2018) that has been reported in human fetal retinas and organoids (Eldred et al, 2018;Hoshino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One distinct cluster upregulates the SLC7A3 and SLC7A5 genes. SLC7A5 is a known thyroid hormone transporter for its T3/T4 states (Scalise et al, 2018) that has been reported in human fetal retinas and organoids (Eldred et al, 2018;Hoshino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…YBX3 translation is reduced upon inhibition of mTORC1 by the specific inhibitor Torin-1 (Thoreen et al, 2012), suggesting that YBX3 expression is potentially regulated by cellular amino acids by mTORC1 activity, which, in turn, regulates SLC transporter expression and the import of essential amino acids. There are numerous examples of physiological and pathological conditions that require increases in SLC expression, including T cell activation, cell growth, and development, as well as cancer and inflammatory diseases (Fotiadis et al, 2013;Ren et al, 2017;Scalise et al, 2018). For example, SLC7A5 and SLC3A2 expression rapidly increase in human skeletal muscle after essential amino acid ingestion, which was suggested to be an adaptive response needed to increase amino acid uptake after eating (Drummond et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, mTOR-associated xenophagy is limited by the uptake of essential amino acids such as leucine (62); because amino acid transportation is limited by glutamine, and glutamine metabolism is altered in metastatic cell lines such as HeLa, Shigella studies of amino acid starvation and xenophagy are constrained by physiologically relevant model systems. In generalized amino acid starvation studies, autophagy is governed by the ATF4-mediated regulation of SLC7A5, a heterodimeric antiporter which couples the influx of leucine/isoleucine with the efflux of glutamine (63,64). Because S. flexneri infection depletes host leucine and isoleucine and activates ATF3, likely through the ATF4 stress response (60), we hypothesized that SLC7A5 is upregulated during S. flexneri infection of colonoid monolayers.…”
mentioning
confidence: 99%